The extensive set of accessory Pseudomonas aeruginosa genomic components. Issue 2 (12th May 2014) - Pohl, Sarah; Klockgether, Jens; Eckweiler, Denitsa; Khaledi, Ariane; Schniederjans, Monika; Chouvarine, Philippe; Tümmler, Burkhard; Häussler, Susanne
Abstract Up to 20% of the chromosomal Pseudomonas aeruginosa DNA belong to the so‐called accessory genome. Its elements are specific for subgroups or even single strains and are likely acquired by horizontal gene transfer (HGT). Similarities of the accessory genomic elements to DNA from other bacterial species, mainly the DNA of γ‐ and β‐proteobacteria, indicate a role of interspecies HGT. In this study, we analysed the expression of the accessory genome in 150 clinical P. aeruginosa isolates as uncovered by transcriptome sequencing and the presence of accessory genes in eleven additional isolates. Remarkably, despite the large number of P. aeruginosa strains that have been sequenced to date, we found new strain‐specific compositions of accessory genomic elements and a high portion (10–20%) of genes without P. aeruginosa homologues. Although some genes were detected to be expressed/present in several isolates, individual patterns regarding the genes, their functions and the possible origin of the DNA were widespread among the tested strains. Our results demonstrate the unaltered potential to discover new traits within the P. aeruginosa population and underline that the P. aeruginosa pangenome is likely to increase with increasing sequence information.